Cross-Species Suppression of Hepatoma Cell Growth and Migration by a Schistosoma japonicum MicroRNA - Yu Lin; Shanli Zhu; Chao Hu; Jing Wang; Pengyue Jiang; Liufang Zhu; Zhengli Li; Sai Wang; Yuanbin Zhang; Xindong Xu; Weiqing Pan (Elsevier, 2019)
Schistosoma japonicum eggs trapped in host liver secretes microRNA (miRNA)-containing extracellular vesicles (EVs) that can be transferred to host cells. Recent studies demonstrated that miRNAs derived from plants can modulate gene expression and phenotype of mammalian cells in a cross-kingdom manner. In this study, we identified a Schistosoma japonicum miRNA (e.g., Sja-miR-3096) that is present in the hepatocytes of mice infected with the parasite and has notable antitumor effects in both in vitro and in vivo models. The Sja-miR-3096 mimics suppressed cell proliferation and migration of both murine and human hepatoma cell lines by targeting phosphoinositide 3-kinase class II alpha (PIK3C2A). We generated a murine hepatoma cell line that stably expressed the pri-Sja-miR-3096 gene and demonstrated cross-species processing of the schistosome pri-miRNA to the mature Sja-miR-3096 in the mammalian cell. Importantly, inoculation of this cell line into the scapula and livers of mice led to a complete suppression of tumorigenesis of the hepatoma cells. Moreover, tumor weight was significantly reduced on intravenous administration of Sja-miR-3096 mimics. Thus, the schistosome miRNA-mediated antitumor activity occurs in host liver cells during schistosome infection, which may strengthen resistance of host to liver cancer, and discovery and development of such miRNAs may present promising interventions for cancer therapy. Keywords: schistosomiasis, Sja-miR-3096, cancer, cross-species regulation, PIK3C2A